2020
DOI: 10.1534/g3.120.401476
|View full text |Cite
|
Sign up to set email alerts
|

Detecting New Allies: Modifier Screen Identifies a Genetic Interaction BetweenImaginal disc growth factor 3andcombover, a Rho-kinase Substrate, During Dorsal Appendage Tube Formation inDrosophila

Abstract: Biological tube formation underlies organ development, and when disrupted, can cause severe birth defects. To investigate the genetic basis of tubulogenesis, we study the formation of Drosophilamelanogaster eggshell structures, called dorsal appendages, which are produced by epithelial tubes. Previously we found that precise levels of Drosophila Chitinase-like proteins (CLPs), encoded by the Imaginal disc growth factor (Idgf) gene family, are needed to regulate dorsal-appendage tube closure and tube migration.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Individual IDGF3 knockdown via RNAi resulted in cuticle molting defects (Zurovcova et al, 2019). In similar studies, Espinoza and Berg (2020) found that overexpressing IDGF3 leads to defects in the dorsal appendage with ∼50% frequency.…”
Section: Discussionmentioning
confidence: 86%
“…Individual IDGF3 knockdown via RNAi resulted in cuticle molting defects (Zurovcova et al, 2019). In similar studies, Espinoza and Berg (2020) found that overexpressing IDGF3 leads to defects in the dorsal appendage with ∼50% frequency.…”
Section: Discussionmentioning
confidence: 86%